2017
DOI: 10.1155/2017/7648505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chimonanthus nitens Oliv. Leaf Extract on Glycolipid Metabolism and Antioxidant Capacity in Diabetic Model Mice

Abstract: The paper investigated the antihyperglycemic and antihyperlipidemic efficacy and antioxidant capacity of Chimonanthus nitens Oliv. leaf extract (COE) in combination of high-glucose-fat diet-fed and streptozotocin-induced diabetic model mice. Various physiological indexes in diabetic model mice were well improved especially by oral administration of high dose of COE; the results were listed as follows. Fast blood glucose (FBG) level and serum triglyceride (TC), total cholesterol (TG), low-density lipoprotein ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Nevertheless, it has been reported that synthetic antioxidants are restricted due to their potential carcinogenicity [3]. Hence, there has been more and more interests in developing and using natural, effective, safe, and multiple biological antioxidants to replace synthetic antioxidants in many industries, such as natural plant polyphenol compounds [4,5]. The flavonoids are a group of polyphenol compounds with a basic structure of C6-C3-C6 carbon skeleton and known for powerful antioxidant capacities based on their polyhydroxyl structures [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been reported that synthetic antioxidants are restricted due to their potential carcinogenicity [3]. Hence, there has been more and more interests in developing and using natural, effective, safe, and multiple biological antioxidants to replace synthetic antioxidants in many industries, such as natural plant polyphenol compounds [4,5]. The flavonoids are a group of polyphenol compounds with a basic structure of C6-C3-C6 carbon skeleton and known for powerful antioxidant capacities based on their polyhydroxyl structures [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Ch. nitens have focused on its calycanthine, chimonanthine, coumarins, flavonoids, phenolic acids, terpenoids, and volatile oils [45,46,47] and their pharmacologies (anti-inflammatory properties [48], antihyperglycaemic [49] and antihyperlipidaemic efficacies, and antioxidant capacity [50], inhibitory α-glucosidase activity [51], and toxicity [52]), phylogeography [45,53], and fingerprints [54,55]. Studies on Ch.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the findings from our previous studies showing that MA inhibited DPPH (a marker of nitrogen radical) in vitro and LPS-induced hepatic NO content in rats ( 13 , 26 ). SOD, GSH-Px, and CAT play an important role in preventing O 2 − and H 2 O 2 -induced oxidative damage ( 27 ). MDA is one of the biomarker of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%